2016
DOI: 10.1371/journal.pone.0157872
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Bivalent DNA Vaccine of α1-Giardin and CWP2 Delivered by Attenuated Salmonella typhimurium Reduces Trophozoites and Cysts in the Feces of Mice Infected with Giardia lamblia

Abstract: BackgroundGiardia lamblia is one of the most common infectious protozoans in human that may cause diarrhea in travelers. Searching for antigens that induced effectively protective immunity has become a key point in the development of vaccine against giardiasis.Methodology/Principal FindingsMice vaccinated with G. lamblia trophozozite-specific α1-giardin DNA vaccine delivered orally by attenuated Salmonella typhimurium SL7027 elicited 74.2% trophozoite reduction, but only 28% reduction in cyst shedding compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The vaccine reduces cyst shedding and transmission of G. lamblia in mice but has no effect on the disease-causing trophozoites (50,51). Another antigen, ␣1-giardin, has been shown to reduce trophozoite load upon immunization with a live recombinant Salmonella-based vaccine vector (52) and after DNA vaccination (53). Independent identification and testing of this antigen as a purified protein in the present study confirmed and expanded these findings.…”
Section: Discussionsupporting
confidence: 77%
“…The vaccine reduces cyst shedding and transmission of G. lamblia in mice but has no effect on the disease-causing trophozoites (50,51). Another antigen, ␣1-giardin, has been shown to reduce trophozoite load upon immunization with a live recombinant Salmonella-based vaccine vector (52) and after DNA vaccination (53). Independent identification and testing of this antigen as a purified protein in the present study confirmed and expanded these findings.…”
Section: Discussionsupporting
confidence: 77%
“…A human vaccine is currently unavailable, and while there is a licensed commercial vaccine for dogs called Giardia Vax®, it has been discontinued in Europe due to insufficient scientific evidence of efficacy [36,37]. Thus, there has been growing interest among the scientific community and pharmaceutics for the identification and characterization of Giardia antigens that may be used as vaccine targets, including variant-specific proteins (VSPs), immunoglobulin binding protein (BIP), excretory-secretory products (ESPs), the annexin homolog α1-giardin, and cell wall protein 2 (CWP-2) [31,35,[38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have demonstrated that α-1-giardin not only stimulates the production of anti-Giardia antibodies (IgA and IgG2a) but also establishes protection against posterior challenges [11]. In addition, not only has the potential use of α-1-giardin been reported as a diagnostic biomarker in several commercial RDTs, such as the Triage Parasite Panel (BioSite Diagnostics, USA) but also additional findings on conserved amino acid and immunological crossreactivity of various Giardia isolates support the continued development of α-1-giardin as an antigenic candidate for a vaccine against giardiasis [26][27][28][29].…”
Section: Protein Biomarkersmentioning
confidence: 99%